Applications of virtual reality in design and simulation of holonic manufacturing systems: A demonstration in die-casting industry - Bal, Mert; Hashemipour, Majid (Springer-Verlag Berlin, 2007)
This paper presents the concepts and the techniques of implementation of Virtual Reality (VR) - based simulations into the design of the Holonic Manufacturing Systems. An integrated methodology is presented, which has been developed for modelling and simulations of a manufacturing system with holonic control with the aid of VR. The main focus is given to the implementation in small and medium size enterprises (SMEs) using limited expertise and minimum costs. To demonstrate the effectiveness of the presented method, an application in a medium-sized die-casting factory is presented. The overall performance of the factory has been tested for implementation of a robot-arm integrated die casting cell with holonic control architecture. In this regard, the best course of action for enterprise's investment decisions has been investigated with the least disruption to existing production activities.
3rd International Conference on Industrial Application of Holonic and Multi-Agent Systems -- SEP 03-05, 2007 -- Regensburg, GERMANY
Keywords: virtual reality; holonic manufacturing; 3-d modelling; simulation.